2008
DOI: 10.2174/1874279300802010027
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology and Risk Factors Of Blood-Borne Virus Infections Among Drug Users in Uppsala County, Sweden

Abstract: Abstract:The prevalence, risk factors, and prevention opportunities of hepatitis A, B, C and HIV infection was studied in injecting drug users (IDUs) in comparison with non-injecting drug users (n-IDUs) in Uppsala County, Sweden.The seroprevalence among IDUs were 0.7% for HIV, 19% for HAV, 26% for HBV and 63% for HCV. For hepatitis C, the seroprevalence was directly related to the number of years of injections. No cases of HIV were found among the nIDUs and the seroprevalence rate was significantly lower for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The prevention of HCV infection is also a major public health concern because infected individuals are 75–85% more likely to develop chronic liver disease ( 20 ). We have previously shown that for hepatitis C, the sero-prevalence among IDUs was directly related to the number of years of injections ( 21 ). The role of the social network of IDUs in HCV transmission has been previously studied by another group ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of HCV infection is also a major public health concern because infected individuals are 75–85% more likely to develop chronic liver disease ( 20 ). We have previously shown that for hepatitis C, the sero-prevalence among IDUs was directly related to the number of years of injections ( 21 ). The role of the social network of IDUs in HCV transmission has been previously studied by another group ( 22 ).…”
Section: Discussionmentioning
confidence: 99%